Using the equity valuation model in determining the acceptable level of income. (Journal of Economic Research & Business Administration, 2015)
The capital assessment model to determine the acceptable level of income play a major role exponent estimates that affect the structure of the model. It is important to correctly place priorities and objective use of market-based instruments. This model is the need for economic and financial services of any enterprise to determine its effective operation.The article offers an acceptable level of income calculation sanalizom discount rate using the weighted average cost of capital, which at the moment is very important for any company.